A Review on Sample Population, Sample Size and Region selected for research on Academic Buoyancy - Singh , Sarab Tej; Kumar, Satish (International Journal of Psychosocial Rehabilitation, 2020)
This review article has been developed on the basis of earlier studies about academic buoyancy. This article consists of summarised view of sample size and sample population and countries where the researches of buoyancy have been administered. Number of research gaps are discussed in the conclusion. There is a need of deep study of buoyancy in late adolescent age in under-developed countries. The sample population in most of the earlier studies is primary and secondary school students (male and female). Only few researches include college students and adults.